Optimization of pet particle-reinforced epoxy resin composite for eco-brick application using the response surface methodology - Mohamad, Effendi; Adiyanto, Okka; Jaafar, Roshidah; Muhammad Faishal; Irianto; Rasyid, Muhammad Izzudin (MDPI, 2023)
Brick is a common building material that is used in society for constructing buildings. A viable environmental strategy to lessen the amount of plastic waste involves the inclusion of plastic trash in building materials. Globally, there is a severe issue with the disposal of plastic garbage in landfills. The primary and secondary carbon bonds that are formed in plastic packaging wastes can severely contaminate the environment. Hence, managing plastic waste to generate new and useful items is essential. One of the most practical ways to safeguard the environment is to manufacture eco-bricks from PET waste and epoxy resin. Additionally, as there is no combustion involved in the production of this eco-brick; it does not harm the environment. Eco-brick can be defined as a novel concept and approach to waste management and recycling. Eco-bricks have many advantages, such as easy availability and being environmentally friendly. This study aimed to improve the composition of the eco-brick using a mixture of epoxy resin and PET particles. In this study, a mathematical modelling technique called the Response Surface Method (RSM) was designed using the Central Composite Design (CCD). Variable input factors were used to develop eco-bricks such as mixture ratio (10–90%), particle size (1–5 mm), and drying time (1–7 days), whereas the variable response included the compressive strength. The complete experimental design was developed using Design Expert 11 software, and simulation experiments with 17 sets of parameters were generated. The microstructural characteristics of the eco-brick were examined using SEM. The results of the experiments indicated that the most optimised parameters that could be used for eco-brick application were: a PET particle size of 1.1 mm, a mixing ratio of 89.9%, and a curing time of 6.9 days. Earlier research that was conducted regarding the production of eco-bricks using a PET particle and epoxy resin mixture showed that these materials had a high potential to boost compressive strength. The quadratic model was used as the basis for the regression analysis for generating the response equations. Since the difference between the experimental and anticipated values was less than 5%, it was concluded that the results of the experimental and predictive tests showed good agreement. The model used in this study yielded noteworthy outcomes. As a result, the suggested statistical model can offer a clear understanding of designing experiments and variables that affect the production of eco-brick using a blend of PET particles and epoxy resin.